D-CreEA: DSML for Creating Educational Analog Card Games - Silva, Rubens Anderson de S.; Andrade, Rossana M. C. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2021: Anais do XX Simpósio Brasileiro de Jogos e Entretenimento Digital, 2021)
Educational games can promote a playful learning experience by solving problems related to the subject of a discipline and assign a student as the main actor in the learning process. In addition, when using analog educational games, this experience provides a face-to-face discussion on the subject, with tactile interaction and quick feedback. However, creating an educational game is difficult, because it demands a scientific, educational basis and game design background. MDE (Model-Driven Engineering) concepts have been used in game development as a promising way to ease the dev process as it helps to develop these games in a standardized and semi-automated way. Hence, the objective of this work is to develop a Domain-Specific Modeling Language for Creating Educational Analog Card Games, called D-CreEA. With this, we provided an approach to aid the process of generating games grounded on the core ideas of card games design by the professor or the game developer, who aims to implement a playful learning methodology, with personalized educational content.